Application of response surface methodology to investigate the effect of different variables on conversion of palm kernel shell in steam gasification using coal bottom ash - Shahbaz, M. (Elsevier Ltd, 2016)
This study has been conducted to investigate the effect of four operating variables that include temperature, particle size, CaO/biomass ratio and weight percentage of coal bottom ash and their interaction on palm kernel shell (PKS) conversion and gasification rate. Steam was used as gasifying agent. Response surface methodology (RSM) was used to study the influence of each factors as well as their combined interactive effect on the conversion and reactivity. Experimental results showed that biomass conversion (X) varied from 0.69 to 0.91 when all the four factors were varied. Their order of influence is temperature > coal bottom ash wt > CaO/biomass > particle size. Gasification rate (Rn) varies between 0.28 and 0.82 when all the factors were varied. It dropped when the operational values are at 725 °C, 0.90 mm particle size, 1.6 of CaO/biomass and 0.08 wt for coal bottom ash. It was predicted that both temperature and coal bottom ash percentage were the most influential variables. The optimal values for the highest gasification rate were at 692 °C, 0.07 of coal bottom ash wt, 1.42 of CaO/biomass ratio and 0.75 mm particle size. Coal bottom ash was used as the catalyst in the biomass steam gasification based on its composition which consists of CaO, Al2O3, Fe2O3 and K2O3 as evident from the XRF analysis. Both gasification rate and biomass conversion were enhanced in the presence of coal bottom ash. © 2016 Elsevier Ltd